Dinamika Organisasi Mahasiswa: Pengembangan, Komitmen, dan Transformasi di Zaman Modern - Pratama, Andy Riski; Rawati, Mesis; Fajri, Fauzan; Oktaviany, Kiki; Messy, Messy (Jurnal Manajemen & Budaya, 2024)
This research discusses the important role of Student Organizations (ORMAWA) in developing the self, character and knowledge of students in higher education, highlighting the urgency of Ormawa based on education law. The focus is on the concept of organizational commitment, identifying three forms of student engagement attitudes. Student interests as the main driver of participation are analyzed by considering factors such as personal interest, self-development and social contribution. This article also examines Ormawa challenges, such as lack of participation and restrictive campus policies, which have a serious impact on organizational resources and atmosphere. The research method used is descriptive qualitative with data triangulation, with analysis of organizational paradigms, sustainability strategies, and solutions to identified problems. Recommendations for adaptive strategies in the contemporary era, including the use of technology, focus on community involvement, improving program quality, effective promotion and branding, innovation in leadership, and external partnerships are outlined. It is hoped that this article can provide in-depth insight into the role and challenges of Ormawa and become a basis for developing sustainability strategies in accordance with dynamics